An examination of verbal adverbs teaching Lithuanians the Russian language - Drotvinas, L. (Psichologija, 1964)
We use the method of collation to review the main verbal adverbs in the Russian language and the usage cases. Furthermore, an indication of some of the Lithuanian language usage features: verbal adverbs in indirect narrative speech and compound present perfect and present perfect continuous tenses, as well as some verbal adverbs word groups, etc. In these cases, other (participial) verb and noun forms or constructions are generally used in Russian. Thus the various Lithuanian tenses, verb categories, and modalities have other means of expression in Russian: changing verb gender or infinitive, modal words, prepositional construction, composite sentence structure, etc.
Keywords: Verbal adverbs; Lithuanian language; Russian language